Kinerja Akuntansi dan Kinerja Pasar Modal pada Perusahaan dalam Jakarta Islamic Index - Sinarti Sinarti; Ainun Na'im (Politeknik Negeri Batam, 2012)
The objective of this research is to give empirical evidence about two propositions: first is the positive relationship between accounting-based performance (ROE, ROA, ROS, and EVA) and market based performance (Sharpe Measure and Treynor Measure), and second is the negative relationship between financial leverage with accounting-based performance (ROE, ROA, ROS, and EVA) and market-based performance (Sharpe Measure and Treynor Measure). The results of the research show that there is positive relationship between accounting-based performance measured using ROA and ROS with market-based performance measured using Treynor measure. There is also negative relationship between financial leverage and accounting-based performance measured using ROA, ROS, and EVA. The research cannot support the hypothesis that there is negative relationship between financial leverage and market-based performance.